Development of power flow software / Noraini Janah Mohammad Isa - Mohammad Isa, Noraini Janah (2003)
The aim of this project is to develop Graphical User Interfacing (GUI) software to perform the load flow simulation for a power system. The software was developed using Borland C++ 5.02 and Microsoft Visual Basic (VB) Version 6.0. The single line diagram was captured from paint to Visual Basic to call bus and line input data form. The input data was inserted to generate the output consisting of the bus number, bus type, real and reactive power, power generator, the voltage and the total of bus. The load flow program was simulated to get the results of the output of the new voltage, angle and power losses graphically. The IEEE 6-bus system was used as test system for the developed software.